Career planning, school grades, and transitions : the last two years in a German lower track secondary school - Fitzenberger, Bernd [Verfasser]; Licklederer, Stefanie [Verfasser] (My University, 2015)
"In Germany, students in lower track secondary schools (LTSS) typically receive intensive career guidance. Nevertheless, the majority of LTSS student graduates does not start an apprenticeship immediately after graduation. This paper analyzes career planning, school grades, and the first transition after graduation for LTSS students in Freiburg during the late 2000s. Only about 10% of LTSS students start an apprenticeship immediately after graduation. About half, typically those with better grades, participate in additional general teaching (AGT) and rather continue schooling after graduation, expecting that this will improve their future career options. The majority of students with poor school grades, especially male students with a migration background, continue with pre-vocational training, even though career guidance was effective in terms of the career planning activities reported by students. Our results suggest that a focus of career guidance on the immediate start of an apprenticeship after graduation may be misplaced for those students continuing in further schooling. Furthermore, such a focus potentially raises hopes for an immediate start of an apprenticeship among the other students, which may later on be frustrated when a student continues with pre-vocational training." (Authors' abstract, BIBB-Doku)
Vorab veröffentlicht u.d.T. "Skill Formation, Career Planning, and Transitions: The Last Two Years in a German Lower Track Secondary School" (ZEW Discussion Paper No. 14-026)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2.1 Erste Schwelle, in Ausbildung; S 1.3 Berufliche Erstausbildung; S 1.2 Berufsvorbereitung; I 2.1.2.4 Baden-Württemberg; Berufsberatung; Berufsorientierung; Berufseinmündung; Erste Schwelle; Betriebliche Berufsausbildung; Weiterführende Schule; Berufsvorbereitung; Hauptschüler; Schulabgänger; Schulleistung; Freiburg; Baden-Württemberg